2021
DOI: 10.1002/brb3.2116
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdense middle cerebral artery sign in large cerebral infarction

Abstract: Objectives To evaluate if the hyperdense middle cerebral artery sign (HMCAS) is an imaging biomarker for hemorrhagic transformation (HT) and the functional outcome of patients with large cerebral infarctions without thrombolytic therapy. Materials and Methods The clinical and imaging data of 312 patients with large cerebral infarction without thrombolytic therapy were retrospectively analyzed. They were divided into patients who presented with HMCAS (n = 121) and those who did not (non‐HMCAS[n = 168] patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…In this study, results of logistic regression analysis showed that the HMCAS was not an independent predictor of MCI, though some relevant studies have shown a close relationship between the HMCAS and the dependent variable. After multiple CT, CTA, MRI, MRA, and autopsy examinations, the study confirmed that the HMCAS had low sensitivity (only 7.0%−69.0%) and high specificity (85.0%−100.0%) in the diagnosis of cerebral infarction ( 12 , 19 – 21 ). Cerebral infarction may be diagnosed if the HMCAS is present ( 14 , 22 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In this study, results of logistic regression analysis showed that the HMCAS was not an independent predictor of MCI, though some relevant studies have shown a close relationship between the HMCAS and the dependent variable. After multiple CT, CTA, MRI, MRA, and autopsy examinations, the study confirmed that the HMCAS had low sensitivity (only 7.0%−69.0%) and high specificity (85.0%−100.0%) in the diagnosis of cerebral infarction ( 12 , 19 – 21 ). Cerebral infarction may be diagnosed if the HMCAS is present ( 14 , 22 ).…”
Section: Discussionmentioning
confidence: 65%
“…The earlier the CT examination is performed, the higher specificity and the lower sensitivity of its findings ( 13 – 16 ). In addition, obscuration of the lentiform nucleus appears within 4–6 h, and the HMCAS appears within 30 min of onset; these findings have a specificity of 85.0%−100.0% ( 12 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 92%
“…Our study that the presence of proximal HMCAS was independently associated with greater odds of HT in patients who receive EVT for acute MCA occlusion. The association between this sign and HT has also been demonstrated in large cerebral infarction patients without thrombolytic therapy and in patients who received IVT [11,12]. In addition, another two studies focusing on the prognostic value of HMCAS on treatment outcomes of EVT found that patients with HMCAS had a higher rate of sHT after the surgery despite statistical insigni cance [16,17].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, another two studies focusing on the prognostic value of HMCAS on treatment outcomes of EVT found that patients with HMCAS had a higher rate of sHT after the surgery despite statistical insigni cance [16,17]. Previous studies have demonstrated that HMCAS on initial NCCT was associated with larger cerebral infarction volume measured by the "one-third of the MCA territory" principle or ASPECTS [9][10][11][12], which is established risk factor of HT after EVT [5][6][7]. In our study, patients with proximal HMCAS had lower ASPECTS on initial NCCT, and proximal HMCAS was independently associated with an increased risk of HT after being adjusted for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation